Motivational differences in online identity reconstruction: A comparative study between China and Malaysia / Jiao Huang - Jiao , Huang (2019)
Social network platforms (such as Facebook and QQ) provide people with a unique opportunity to communicate and interact with others. Individuals are able to construct their own profile and share messages, photos or other media with their friends online. Given that individuals have control over what to post on social network platforms, it is possible that they may reconstruct an online identity that is partly or totally different from their real identity. In this case, with a reconstructed online identity, people are able to become more attractive, express themselves more freely and better protect their privacy. Previous studies have suggested that people may reconstruct an online identity due to various reasons (such as vanity, bridging social capital, disinhibition, and privacy concerns). However, it is not clear whether people of different genders and from different countries are motivated differently when it comes to identity reconstruction on social network platforms. Adopting social role theory and Hofstede’s cultural dimension framework as the theoretical background, the present study aims to identify gender and cultural differences in the motivations for identity reconstruction on social network platforms in two countries: China and Malaysia. An online survey was conducted to collect data. A total of 815 respondents (418 Chinese and 397 Malaysians) participated in this study. T-test and ANOVAs were used to analyze the data. Gender differences in the motivations for identity reconstruction were examined in the Chinese and Malaysian samples respectively. The results revealed that gender differences in the Chinese sample were more salient than in the Malaysian sample. Specifically, Chinese men and women were motivated differently by all the four factors, whereas few gender differences were found between the Malaysian men and women. For example, Chinese men were more likely to be motivated by achievement vanity and less likely to be motivated by physical vanity than Chinese women. Cultural differences were examined between the Chinese and Malaysian samples, as well as between different ethnic groups (such as between the Malaysian-Chinese and the Malaysian-Malays). Significant differences were identified. In comparison with Malaysian people, Chinese people were more likely to be motivated by bridging social capital and disinhibition when reconstructing their identity on social network platforms, but less likely to be motivated by physical vanity and privacy concerns. The Malaysian-Malays were more likely to be motivated by physical vanity and bridging social capital than the Malaysian-Chinese when they reconstruct their identity on social network platforms. Theoretically speaking, this study extends the research of online identity reconstruction by taking gender and national culture into account. It also contributes to the cross-cultural research concerning social network platforms. The findings of this study also add knowledge to the research on gender and shed light on the specific culture of China and Malaysia. Practically speaking, the results of this study can provide guidelines for practitioners when it comes to deploying suitable strategies for different groups of users to better fulfill their needs.